Developments in cognitive socialization: implications for deaf education. - Muma JR; Teller H (American Annals of the Deaf, 2001)
Over the past 2 to 3 decades, the cognitive socialization literature has advanced about 40 major issues that could have a major impact on the principles and procedures of deaf education. The article presents a conceptual model of the cognitive social bases of language that is derived from the philosophical view of constructionism and theoretical perspectives of speech act theory and relevance theory. With the cognitive socialization perspective and this conceptual model, 4 of the 40 issues are discussed: (a) the centrality of intent replacing reinforcement as a more viable account of language acquisition, (b) modality and core issues of language, (c) lack of construct validity in assessment, and (d) heterogeneity. Implications for the advancement of deaf education are discussed throughout.